Sulfide-induced supported metal nanoclusters, methods of making and using the same

CN118304939BActive Publication Date: 2026-10-20TONGJI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410417129.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-08
Publication Date
2026-10-20
Estimated Expiration
2044-04-08

AI Technical Summary

Technical Problem

同样,采用配体交换法也非常难,因为弱配体很难将强配体交换下来

Benefits of technology

[0032](1)由于硫醇的引入,使金属原子一旦生成就很容易被捕捉而成核;而成核效率越高,最终金属纳米颗粒尺寸越小,比表面积越大,催化效率越高,即由于微量硫醇的引入,金属原子成核显著提高,催化效率相应显著提高。比如在每个PEI上引入2个硫醇基,金属成核效率提高93倍;引入3个硫醇基,金的成核效率提高196倍,从而具有超高催化活性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118304939B_ABST
    Figure CN118304939B_ABST
Patent Text Reader

Abstract

The present application provides a sulfide-induced supported metal nanocluster and its preparation method and application. The metal nanocluster usually needs to be generated under harsh conditions, and the catalytic activity is often inhibited by ligands. The present application shows that trace mercaptan not only will not become a toxic agent, but will activate the metal nanocluster. At the same time, these mercaptans are very effective metal nucleating agents, which can directly modulate metal nanoclusters. Hyperbranched polyethyleneimine is loaded on a porous polymer carrier in any way; trace mercaptan is covalently introduced on the loaded polyethyleneimine; potassium tert-butoxide is treated in an aprotic polar medium, then a transition metal salt is added and reacted to form a polyethyleneimine-protected supported metal nanocluster. Metal nanoclusters are obtained in the presence of an optimal dose of mercaptan, and the catalytic activity is significantly improved. If a large number of hydrophilic groups are further introduced on the polyethyleneimine, the catalytic activity of the catalyst for water-soluble substrates is further improved, and it is easy to recycle.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of catalytic materials technology, specifically relating to a sulfide-induced supported metal nanoclusters, its preparation method, and its applications. Specifically, it involves modulating highly active supported catalytic metal nanoclusters with trace amounts of thiols or thioethers. Background Technology

[0002] Metal nanoclusters have attracted widespread interest as catalysts in recent years. Their extremely small size (0.1-2.3 nm) and high specific surface area result in higher catalytic efficiency. Furthermore, their Fermi level location and quantum confinement effects lead to more pronounced catalytic activity at specific sizes. However, the catalytic potential of metal nanoclusters has not yet been fully realized. This is because the catalytic activity of metal nanoclusters is largely determined by ligand properties, but most current metal nanoclusters are protected by a single strong ligand, which is difficult to remove, making it challenging to fully optimize ligand parameters.

[0003] The electronic properties, geometry, and solubility of ligands influence the catalytic activity of metal nanoclusters. Among these, the electronic effect has received increasing attention in recent years. For example, studies have found that after adsorbing a small amount of thiol (only 20% coverage) onto the surface of gold particles, the gold no longer adsorbs hydrogen. This result indicates that spatial factors are not the key to adsorption in this case; electronic properties are. Similarly, CO is not adsorbed on the surface of gold ingots, but if NO2 is pre-adsorbed on the surface, CO will be adsorbed. Furthermore, Pt nanoparticles modulated with oleylamine show low activity in catalyzing the oxygen reduction reaction (ORR), but a small amount of oleylamine can actually improve their catalytic activity. Metal nanoparticles protected by weak ligands generally exhibit higher catalytic activity compared to their counterparts protected by strong ligands. This is because weak ligands allow the active sites of the metal to be fully exposed, thus better catalytically exerting their effect. However, it is difficult to modulate ultra-small metal nanoclusters with weak ligands due to their low ability to capture metal atoms and their weak nucleation ability. Thiols are typical strong ligands, which are conducive to metal atom nucleation. Meanwhile, thiols are also well-known poisons for metal catalysts, often severely inhibiting the catalytic activity of metals; to our knowledge, no counterexamples have been found to date. Thiols are typical soft bases, exhibiting strong coordination or covalent interactions with zero-valent transition metals, consistent with the theory of soft acid-soft base affinity. The inhibitory effect of thiols on metal catalysis is generally attributed to two viewpoints: one is that thiols occupy active sites; the other is that they are influenced by electronic effects.

[0004] The synthesis of metal nanoclusters is typically complex, due to its demanding synthesis conditions. For example, it often requires large amounts of strong ligands or expensive nanotemplates. In 2021, Wan Decheng et al. disclosed a patent for the modulation of metal nanoclusters using sulfide (Trace Sulfide-Assisted Modulation of Loaded Gold Nanoclusters with Polymer Patches and Its Catalytic Effect, ZL 2021 10309232.5), revealing that trace amounts of sulfide can effectively assist in the modulation of metal nanoclusters, avoiding the use of strong ligands or expensive templates. However, the nucleation effect of sulfide is not strong enough, resulting in insufficient gold loading. This patent also does not mention the effect of trace amounts of sulfide on the catalytic efficiency of the metal.

[0005] Finding a ligand that can both efficiently modulate metal nanoclusters (with strong nucleation ability) and endow them with high catalytic activity appears quite difficult at present. Abandoning the traditional single-ligand concept is one strategy, but physically mixing strong and weak ligands to achieve this strategy will undoubtedly fail, as strong ligands always preferentially interact with metals. Similarly, ligand exchange is also very difficult, because weak ligands rarely exchange strong ligands. However, covalently integrating a small number of strong ligands onto a large number of weak ligands might change this situation. Finally, as a catalyst, recyclability is a key parameter, not only facilitating catalyst reuse but also improving the quality of the final product. Summary of the Invention

[0006] To address the shortcomings of existing technologies, the first objective of this invention is to provide a method for preparing sulfide-induced supported metal nanoclusters, designing a metal ligand that possesses both strong metal nucleation ability for direct synthesis of metal nanoclusters and improved catalytic efficiency of the metal nanoclusters. On one hand, thiols readily capture zero-valent metal atoms, making them strong metal nucleating agents. On the other hand, the optimized combination of the electron-withdrawing ability of a small amount of thiol and the electron-donating ability of a large number of ligands can potentially stimulate the catalytic activity of the metal. Therefore, this objective can be achieved through dosage optimization and multi-ligand integration.

[0007] A second objective of this invention is to provide a sulfide-induced supported metal nanocluster.

[0008] A third objective of this invention is to provide an application of sulfide-induced supported metal nanoclusters, primarily for catalytic reactions of water-soluble substrates. This facilitates water treatment and allows many reactions to be carried out in the green medium of water.

[0009] To achieve the first objective mentioned above, the solution of the present invention is:

[0010] The method for preparing sulfide-induced supported metal nanoclusters of the present invention aims to simultaneously enhance nucleation and impart high catalytic activity to the catalyst by optimizing the dosage of thiols, thereby improving the catalytic reduction ability of metal nanoclusters for aqueous substrates. The method includes the following steps:

[0011] (1) Modification of carrier-supported polyethyleneimine (PEI)

[0012] PEI is loaded onto a porous material with arbitrary covalent bonds; wherein the porous material is a polymer material and is regarded as a carrier, and PEI is regarded as a patch.

[0013] A certain amount of thiol ligands (considered as strong ligands) from sulfides are introduced onto the loaded PEI ligand (considered as weak ligands) patch, thereby modifying the PEI on the support.

[0014] (2) PEI-modified microspheres supporting metal nanoclusters

[0015] The porous material loaded with PEI in step (1) is crushed and dispersed in an aprotic polar solvent. Potassium tert-butoxide is added to eliminate acidic hydrogen, and metal ions are added and mixed and stirred. The mixture is reacted at room temperature so that the PEI ligand patch is wrapped with metal nanoclusters reduced to zero valence, thus obtaining sulfide-induced loaded metal nanoclusters.

[0016] Furthermore, in step (1), the molecular weight of PEI is selected from 2000±500 Da.

[0017] Furthermore, in step (1), the molar dose of sulfide is equivalent to 3-4 mol% of the repeating unit of PEI.

[0018] The sulfides are selected from one or more thiols and thioethers. Thioethers are considered a second-best alternative to thiols, as their synthesis is more convenient. However, the regulatory effect of thioethers is weaker than that of thiols, making them a less than ideal choice. The molar dosage of thiols is equivalent to 4 mol% of the repeating unit of PEI, and the molar dosage of thioethers is equivalent to 3 mol% of the repeating unit of PEI.

[0019] Further, in step (1), the thiol is introduced by reacting cyclothioethane with PEI. The amount of thiol introduced is equivalent to introducing about 2 thiol groups onto each PEI, or equivalent to 4 mol% of the number of amino units in the PEI.

[0020] Furthermore, in step (2), the aprotic polar solvent is N,N-dimethylformamide (DMF).

[0021] Furthermore, in step (2), the molar ratio of the amount of metal ions added to the repeating unit of PEI is 1:6-1:16, that is, the ratio of the number of metal atoms to the number of nitrogen atoms in PEI is 1:6-1:16.

[0022] Further, in step (2), the metal ions are selected from Au, Ag, Pt, Pd, Cu, Ni or Co ions, including but not limited to KAuCl4, AgNO3, K2PtCl4, PdCl2 and nitrates, oxalates or halides of Cu, Ni or Co ions.

[0023] Furthermore, in step (2), the reaction temperature is 25-80℃ and the reaction time is 1-12h.

[0024] In step (2), potassium tert-butoxide is usually in excess, amounting to 1.5 molar equivalents of PEI amino units.

[0025] To achieve the second objective mentioned above, the solution of the present invention is:

[0026] A supported metal nanocluster is obtained by the above preparation method.

[0027] The preparation method also includes hydrophilic modification of the PEI-modified material, specifically:

[0028] The porous material loaded with metal nanoparticles in step (2) is dispersed in water or alcohol, and the residual amino hydrogen on PEI in the porous material is treated with glycerotrimethylammonium chloride as a reactant to convert it into the corresponding hydroxyl and quaternary ammonium salt.

[0029] To achieve the third objective mentioned above, the solution of the present invention is:

[0030] The above-mentioned supported metal nanoparticles are used for the catalytic reduction of various water-soluble substrates.

[0031] Due to the adoption of the above solution, the beneficial effects of the present invention are:

[0032] (1) Due to the introduction of thiols, metal atoms are easily captured and nucleated once they are generated; the higher the nucleation efficiency, the smaller the final metal nanoparticle size, the larger the specific surface area, and the higher the catalytic efficiency. That is, due to the introduction of trace amounts of thiols, the nucleation of metal atoms is significantly improved, and the catalytic efficiency is correspondingly significantly improved. For example, the introduction of 2 thiols on each PEI increases the metal nucleation efficiency by 93 times; the introduction of 3 thiols increases the nucleation efficiency of gold by 196 times, thus exhibiting ultra-high catalytic activity.

[0033] (2) Since PEI-stabilized metal nanoclusters generally have high activity, a large amount of amines makes the surface charge density of metal nanoclusters too high, which is not conducive to catalysis. When an optimized dose of thiol is introduced, the charge density can be reduced, making it very suitable for catalysis, and thus the metal catalyst is activated. However, a slight excess of thiol will make the charge density too low, and the catalytic activity will immediately decrease significantly. Therefore, the dosage of thiol needs to be optimized to activate metal nanoclusters.

[0034] (3) For hydrophilic substrates such as 4-nitrophenol, if a large number of quaternary ammonium salt groups and / or hydroxyl groups are introduced into the ligand layer of the metal catalyst, the substrate affinity will be enhanced. After the ligand layer is chemically modified, the mass transfer rate of the catalytic process is accelerated, and the catalytic efficiency of the metal catalyst is significantly improved.

[0035] (4) Due to the use of large-sized porous microspheres (approximately 170 μm in diameter), the catalytic material is easy to recover. Attached Figure Description

[0036] Figure 1 The diagram and cartoon illustration show the chemical process and cartoon illustration of the generation of gold nanoclusters by introducing thiolation onto a carrier PEI and treating it with potassium tert-butoxide in Example 1 of the present invention.

[0037] Figure 2 The diagrams are chemical schematics and cartoon illustrations of the ligand hydrophilization modification of gold nanoclusters in Example 2 of this invention.

[0038] Figure 3 The figure shows the dependence of the TEM size of the gold nanoclusters on the thiol dosage in Example 1 of the present invention. The amount of thiol introduced was 0 (A), 1 (B), 2 (C) and 3 thiol groups (D) introduced on each PEI, and the resulting gold particle sizes were 6.4±4.0 (A), 2.5±0.8 (B), 1.3±0.4 (C) and 1.1±0.4 nm (D).

[0039] Figure 4 The UV-Vis spectrum (A) and fitted kinetic curve (B) of the catalytic reduction of 4-nitrophenol in Example 2 of this invention are shown below (reaction conditions: [4-NP]0 = 0.06 mmol / L). -1 [NaBH4]0 = 60 mmol / L -1 [Au] = 0.1ppm). Detailed Implementation

[0040] The technical solution of the present invention will be further described in detail below with reference to several embodiments. These embodiments are implemented on the premise of the technical solution of the invention, and detailed implementation methods and specific operation processes are given. However, the protection scope of the present invention is not limited to the following embodiments.

[0041] Unless otherwise specified, the experimental materials used in the examples below can be purchased from conventional biochemical reagent companies.

[0042] This invention modifies PEI supported on a carrier with thiols. The introduction of trace amounts of thiols enhances nucleation, allowing for the direct fabrication of ultra-small metal nanoclusters such as Au, Ag, Pd, Pt, Cu, Ni, and Co. This increases the catalytic efficiency by improving the specific surface area of ​​the metal clusters. Experiments also demonstrate that the presence of trace amounts of thiols can activate the metal nanoclusters by balancing the charge density on the metal catalyst surface. A large amount of glycerotrimethylammonium chloride is used to fully hydrophilize PEI, facilitating the proximity of hydrophilic substrates to the catalyst, accelerating mass transfer, and further improving catalytic efficiency. This design of the ligand layer enables the catalyst to achieve ultra-high catalytic efficiency.

[0043] The present invention will be further described below with reference to the embodiments.

[0044] Example 1

[0045] See implementation route Figure 1 .

[0046] (1) Following the method described in the literature (Wan et al., J Mater. Chem. A, 2021, 9, 15714), PEI was loaded onto porous polymer microspheres via a reaction with chlorophenyl groups on the pore surface of the support. The loading amount was 2.05 mmol N / g (i.e., nitrogen content of 28.7 mg / g), and the specific surface area of ​​the microspheres after loading became 407 m². 2 g -1 The average pore size is 3.7 nm.

[0047] (2) Synthesis of supported gold nanoclusters (chloroaurate is used as an example in this embodiment).

[0048] Synthesis as shown Figure 1 The process was carried out as follows: First, the supported PEI (1 g, 2.05 mmol NH) was dispersed in degassed DMF. A degassed DMF solution of 0.044 mmol cyclothioethane (5 mL) was added dropwise to the dispersion, and the mixture was stirred under nitrogen at room temperature for 6 h. A degassed DMF solution of 0.2 g, 2.2 mmol, 50 eq, cyclothioethane (10 mL) was added to the dispersion after degassed potassium tert-butoxide (0.2 g, 2.2 mmol, 50 eq, cyclothioethane). The mixture was stirred for 0.5 h. A degassed DMF solution of chloroauric acid (0.34 mmol Au, N:Au = 6:1 molar ratio) or an equal molar amount of potassium chloroaurate (1 mL) was added and stirred. After the liquid phase became colorless, the mixture was heated at 80 °C for 1 h. The microspheres were filtered out, washed twice with deionized water, then rinsed with ethanol, and vacuum dried to constant weight (1.058 g). The sample was labeled Au@s-PEI-(SH)1( Figure 1 In the figure, x = 1 indicates that a thiol was introduced onto each PEI, resulting in a gold-loaded nanocluster. The gold loading of this product is 0.32 mmol / g (or 6.3%).

[0049] Au@s-PEI-(SH) x (x=0,2,3) Similar to composition. Figure 3 Gold nanoparticles and gold nanoclusters modulated with different doses of thiols were demonstrated. From Figure 3 The gold particle size can be calculated to show that when 3 thiols are introduced onto each PEI, the metal nucleation efficiency increases by 196 times; if only 2 thiols are introduced (such as... Figure 3 (as shown in Figure C), then it improves by 93 times. The specific algorithm is as follows. When there are 0 thiols in each PEI (e.g., ... Figure 3 (See Figure A in the image). The diameter of the gold particles is D = 6.4 nm, and the number of gold atoms per particle is N = 30.896D. 3 That is, 8099 gold atoms. However, based on the feed amount, each PEI can be allocated 7.75 gold atoms. This means that only 0.96% of the patches contain gold particles. And when each PEI contains 3 thiols (such as...), Figure 3 (See Figure D in the diagram). The diameter of the gold particles is D = 1.1 nm, and each particle contains 41 gold atoms. This means that 18.9% of the patches contain gold particles, indicating an increased nucleation efficiency. These two percentages show a difference of 196 times.

[0050] (3) Supported gold nanoclusters catalyze the reduction of 4-nitrophenol (4-NP).

[0051] Typically, the solution contains NaBH4 (60 mmol L) -1 ) and 4-NP (0.06 mmol L -1 Nitrogen gas was passed through a 1000 mL solution of Au@s-PEI-SH2 (5 mg, containing 1.6 × 10⁻⁶ ppm) for 0.5 h to remove oxygen. -5 mmol or 3.3×10 -4 Add g of gold to the mixture and stir. At regular intervals, take 3 mL of sample for UV / Vis spectral monitoring (after which the sample is returned to the reaction system). The obtained data are processed using the following equation:

[0052] -ln(C t / C0) = -ln(A t / A0)= kt = k s St = k c [Au]t (1)

[0053] Where k is the apparent rate constant (s) -1 ), C0 and C t Indicates the concentrations of 4-NP at times 0 and t; A0 and A t This is the absorbance of 4-NP at 400 nm; k sIt is the area-normalized rate constant, while k c The normalized rate constant for metal concentration, S is the surface area of ​​all gold nanoclusters per unit volume, and [Au] represents the equivalent concentration of gold atoms.

[0054] The operating frequency (TOF) of the catalyst is calculated using the following equation:

[0055] TOF = [4-NP]0 × Conversion rate / ([Au] × t) (2)

[0056] The catalytic efficiency of gold nanoclusters can be evaluated using normalized rate constants, which are summarized in Table 1. As can be seen, both the apparent rate constant and the concentration-normalized rate constant increase significantly when the thiol dosage is gradually increased to 2 thiols per PEI. c It increased by 10.9 times. This increase is likely a result of the smaller gold particles and the significant increase in the specific surface area of ​​gold. Surprisingly, the area normalization constant k... s As the number of thiols per PEI increases from 0 to 2, the constant increases by 140%, indicating that thiols themselves enhance the catalytic activity of gold nanoclusters. Thiols have long been considered poisons for metal catalysts, but here they act as propellants. A likely reason is that the surface electron density of metal nanoclusters reaches its optimal catalytic effect at a certain level; excessively high or low levels are detrimental to catalytic activity. In this system, the large amount of aliphatic amines provided by PEI acts as an electron donor, placing the gold nanocluster surface in an electron-rich state, which is unfavorable for catalysis. The introduction of a small amount of electron-withdrawing thiols can reduce the charge density, improving the catalytic effect. However, a slightly higher concentration of thiols (sample 4 in Table 1) places the gold nanoclusters in an electron-poor state, also hindering catalysis. The catalytic activity is so sensitive to thiols because thiols and gold are soft acid and soft base, with strong interactions. Some might argue that this result is due to the quantum size effect of gold nanoclusters. A comparison of samples 3 and 4 in Table 1 shows that while the size of the gold nanoclusters does not change significantly, their activities differ greatly. Therefore, this possibility is unlikely.

[0057] Table 1 Au@s-PEI-(SH) x Effect of thiol dosage on the rate constant of catalytic 4-nitrophenol reduction. a

[0058]

[0059] a Condition: [4-NP]0 = 0.06 mmol / L -1 [NaBH4]0 = 60 mmol / L -1 [Au] = 0.32ppm; error within 10%.

[0060] Example 2

[0061] like Figure 2 As shown, the catalytic performance of Au@s-PEI-(SH)2, which performed best in Example 1, was evaluated after hydrophilization treatment. Au@s-PEI-(SH)2 (0.5 g, 0.92 mmol NH) was dispersed in ethanol (10 mL), and glyceryltrimethylammonium chloride (69.7 mg, 0.46 mmol) was added and stirred overnight. The microspheres were collected by filtration, washed with deionized water and ethanol, and dried to obtain 565 mg (99%). Elemental analysis showed that the nitrogen content increased from 2.87% to 3.48%, corresponding to the structure: Au@s-PEI-(SH)2-(N+). 22.4 (Where 22.4 indicates that each PEI is attached with 22.4 quaternary ammonium salts). If glycerotrimethylammonium chloride is in excess, Au@s-PEI-(SH)2-(N+) can be obtained. 40 Its catalytic activity was evaluated similarly to that in Example 1. Au@s-PEI-(SH)2-(N+) was used. 40 As a catalyst for the reduction of 4-NP, such as Figure 4 As shown. From Figure 4 As can be seen, at only 0.1 ppm (5.1 × 10⁻⁶), -4 mmol / L -1 In the presence of a gold catalyst, the signal of the 4-nitrophenol anion at 400 nm decreases rapidly, and the conversion rate reaches >98% in only about 5 minutes, from which the apparent rate constant k = 0.015 s is derived. -1 The concentration of gold was normalized to k / (5.1×10). - 4 mmol L -1 = 29.4 L / (mmol·s). The highest catalytic rate constant was derived from this, as shown in Table 2. Table 2 shows that when a large amount of hydrophilic quaternary ammonium salt is introduced onto PEI, k... c It increased by another 91%.

[0062] Spectroscopic monitoring showed that 4-NP can be concentrated by the ligand layer, thereby accelerating the catalytic mass transfer process. The concentration of 4-NP by the ligand layer is mainly driven by hydrogen bonding and electrostatics. The reduction product, 4-aminophenol, is not adsorbed by the ligand layer but directly enters the aqueous phase, without affecting catalysis.

[0063] With the enhancement effect of thiols and the affinity of the ligand layer for the substrate 4-NP, the catalytic activity of gold is improved to an unprecedented degree, and its rate constant is much higher than that of existing similar supported catalysts, as shown in Table 3.

[0064] Table 2. Rate constants for the reduction of 4-NP catalyzed by hydrophilic modified gold nanoclusters. a

[0065]

[0066]

[0067] a Condition: [4-NP]0 = 0.06 mmol / L -1 [NaBH4]0 = 60 mmol / L -1 [Au] = 0.32 ppm; b [Au] = 0.11ppm; c [Au] =

[0068] 0.10ppm.

[0069] Table 3 shows the normalized rate constant k of carrier-supported gold nanoparticles (clusters) reported in the literature. c Comparison with the present invention

[0070]

[0071] literature:

[0072] 1.Comptes Rendus Chimie 2019,22(9),621-627.

[0073] 2.Journal of Colloid and Interface Science 2019,533,161-170.

[0074] 3.Journal of Materials Science 2015,50(3),1323-1332.

[0075] 4.ACS Applied Nano Materials 2022,5(1),1276-1283.

[0076] 5.Catalysis Science&Technology 2023,13(7),2001-2009.

[0077] 6.Journal of Materials Chemistry A 2014,2(36),14807-14811.

[0078] 7.Journal of Materials Chemistry A2017,5(1),230-239.

[0079] 8.ACS Applied Materials&Interfaces 2015,7(39),21717-21726.

[0080] 9.Journal of Materials Chemistry A2021,9,15714.

[0081] 10.Chemical Engineering Journal,2020,390,124485.

[0082] Example 3

[0083] The catalytic reduction of 4-NP by gold nanoclusters modulated with thioethers has been reported (Journal of Materials Chemistry A 2021, 9, 15714). However, whether thioethers can enhance the catalytic activity of gold nanoclusters remains unknown. A re-evaluation was conducted here, with the material synthesis and catalysis performed exactly as described in the aforementioned literature. The re-evaluated rate constants are shown in Table 4.

[0084] Table 4. Rate constants for 4-NP reduction of gold nanoparticles modulated by introducing different doses of thioether into carrierd PEI. a

[0085]

[0086] a [Au] = 0.12 ppm; [4-NP]0 = 0.06 mM; [NaBH4]0 = 60 mM; room temperature; b PS x -Au: thioether-functionalized PEI modulated gold particles; x represents the number of thioethers on each PEI.

[0087] Table 4 shows that the introduction of thioethers did not inhibit catalytic activity; on the contrary, it enhanced it to some extent. The principle is essentially the same as that of thiols. Similarly, thioethers can also enhance metal nucleation. However, overall, the effect of thioethers is not as strong as that of thiols. Therefore, the metal loading did not increase significantly after the introduction of thioethers; the nucleation effect of thioethers on metals was also not strong enough. Calculations show that introducing three thioethers onto each PEI increased the metal nucleation efficiency by 13 times, far less than the 196 times increase caused by the same amount of thiols.

[0088] Example 4

[0089] In Example 1, the reduction of 4-NP was completed in just 3 minutes using the cationic dye x-GTL instead of 4-NP. In the absence of a catalyst, it took 8 minutes. Due to the scarcity of literature on the reduction of this dye, a comparison of the catalytic rate constant is not possible. However, this at least demonstrates that cationic catalysts can accelerate the reduction of cationic dyes, meaning the catalyst is applicable to a wide range of substrates.

[0090] Example 5

[0091] In Example 2, Pt was used instead of Au to synthesize Pt@s-PEI-(SH)2-(N+). 40 Platinum nanoclusters with a size of 1.2 nm were obtained, and their concentration-normalized rate constant k for catalyzing the reduction of 4-NP was determined. c =29.7 L mmol -1 s -1 This is the highest value reported to date among similar supported catalysts. This indicates that thiols also exhibit high metal nucleation efficiency for platinum. The area normalization rate reaches 58.8 × 10⁻⁶. -2 Lm -2 s -1 It is also the highest known value, as shown in Table 5.

[0092] Table 5. Rate constants (k) of platinum catalysts normalized to their surface area as reported in the literature. s )

[0093]

[0094]

[0095] A: Data are from Applied Catalysis A:General, 2015, 497, 107-120 and the references cited therein.

[0096] B: Data are from J.Phys.Chem.C 2013, 117, 44, 22644–22651 and the references cited therein.

[0097] Example 6

[0098] In Example 2, a similar synthesis was performed using nickel, copper, and cobalt instead of gold, with corresponding metal particle sizes between 1.8 and 2.8 nm, and a concentration-normalized catalytic rate constant k. c In 0.06-0.7 L mmol -1 s -1 Compared to literature reports, this represents a significant improvement.

[0099] The above description of the embodiments is intended to enable those skilled in the art to understand and use the present invention. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.

Claims

1. A method for preparing sulfide-induced supported metal nanoclusters, characterized in that: It includes the following steps: (1) Modification of carrier-supported polyethyleneimine Covalent loading of polyethyleneimine onto porous materials; Sulfide ligands are covalently introduced onto polyethyleneimine supported on porous materials to modify polyethyleneimine, thus creating porous materials supported on polyethyleneimine. (2) Metal nanoclusters supported on polyethyleneimine modified microspheres The porous material loaded with polyethyleneimine in step (1) was dispersed in an aprotic polar solvent, and the acidic protons in the system were removed with potassium tert-butoxide. Then it was mixed and stirred with metal ions and reacted at room temperature, so that the polyethyleneimine patch was wrapped with metal nanoclusters reduced to zero valence, and sulfide-induced loaded metal nanoclusters were obtained. In step (1), the molar dose of the sulfide is equivalent to 3-4 mol% of the repeating unit of polyethyleneimine, and the sulfide is a thiol; In step (1), the sulfide ligand is introduced by reacting cyclothioethane with polyethyleneimine; In step (2), the aprotic polar solvent is N,N-dimethylformamide; In step (2), the metal ions are selected from Au, Ag, Pt, Pd, Cu, Ni or Co ions.

2. The method for preparing sulfide-induced supported metal nanoclusters according to claim 1, characterized in that: In step (1), the molecular weight of the polyethyleneimine is selected from 2000. 500Da.

3. The method for preparing sulfide-induced supported metal nanoclusters according to claim 1, characterized in that: In step (2), the molar ratio of the amount of metal ions added to the repeating polyethyleneimine unit is 1:6 to 1:

16.

4. The method for preparing sulfide-induced supported metal nanoclusters according to claim 1, characterized in that: In step (2), the reaction temperature is 25-80 °C and the reaction time is 1-12 h.

5. A sulfide-induced supported metal nanocluster, characterized in that, It is obtained by the preparation method described in any one of claims 1-4.

6. A sulfide-induced supported metal nanoclusters as described in claim 5 for the catalytic reduction of water-soluble substrates.

Citation Information

Patent Citations

  • Microscale thioether assisted polyamine patch modulated and loaded gold nano-cluster and catalytic application thereof

    CN113070100A

  • Multi-dimensional ligand layer design and preparation method, ultrahigh catalytic activity metal nanoparticles and application

    CN116920945A